Pengaruh Ukuran Kapasitor Paralel Belitan Utama Terhadap Keluaran Generator Induksi 6 Kutub - Pangestu, Chandra Murdian; , Agus Supardi, S.T., M.T (2016)
The adverse effects of conventional power plants can cause environmental pollution and the depletion of fossil fuels. This problem must be resolved by begin to minimize the use of conventional power plants and start to use renewable electricity generation. The use of induction generator on small-scale renewable electricity generation can be a solution to reduce the adverse effects of conventional power plants. The purpose of this study is to observe the effect of variations in the value of the parallel capacitor to the output of induction generator. The capacitors are arranged in parallel and connected to the main winding of induction generator. Observations were made when the generator at no load condition and connected load condition and rotated at 1000 and 1050 rpm. Load used is a resistive load with a value of 40, 80, 120, 160, and 200 watts. The induction generator used in this study had 6 poles and a capacity of 1 HP. Parallel capacitors used in the test has a value of 48, 56, 64, 72, and 80 μF. The test results showed in no load condition and generator is rotated at a speed of 1000 rpm. The voltage and frequency is 220 volts and 49.9 Hz at 72 μF capacitor value. For speed of 1050 rpm, the highest voltage and frequency is 249.8 volts at 80 μF capacitor and 52.8 Hz at 72 μF capacitor. At loaded conditionand speed of 1000 rpm the highest voltage is 179.9 volts at 72 μF capacitor values.The largest current is 0.63 amperes at 80 μF capacitor value. The highest frequency is 48.9 Hz at 72 μF capacitor. At loaded condition on speed 1050 rpm the highest voltage and current is 227.6 volts on the capacitor value of 80 μF and 0.76 amperes at 64 μF capacitor value. For the greatest frequency is 50.8 Hz with a value of 80 μF capacitor.